1986
DOI: 10.1055/s-2007-1020381
|View full text |Cite
|
Sign up to set email alerts
|

Damage of Porcine Aortic Valve Tissue Caused by the Surfactant Sodiumdodecylsulphate

Abstract: The Hancock T6 treatment uses 1% sodiumdodecylsulphate (SDS) to prevent or delay calcification in porcine aortic or pericardial bioprostheses. In the current study fresh and glutaraldehyde fixed porcine aortic cusps were treated in 1% SDS. The hydrothermal stability, the histological and the electronmicroscopic appearance of the tissue were assessed and compared before and after treatment. The results suggest that the 1% SDS solution destroys the fresh material causing acellularity, extreme fragmentation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…Before doing transplantation in humans, the safety of the implant materials must be considered seriously. Multiple studies have established that residual SDS in the tissue causes cytotoxicity (Bodnar et al, 1986;Rieder et al, 2004;Mirsadraee et al, 2007). However, it was noted in our previous study that no cytotoxic effects were observed among normal cells treated with the decellularized pericardial extract.…”
Section: Discussionmentioning
confidence: 82%
“…Before doing transplantation in humans, the safety of the implant materials must be considered seriously. Multiple studies have established that residual SDS in the tissue causes cytotoxicity (Bodnar et al, 1986;Rieder et al, 2004;Mirsadraee et al, 2007). However, it was noted in our previous study that no cytotoxic effects were observed among normal cells treated with the decellularized pericardial extract.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, the loss of collagen on quantitative assay correlates with loss of UTS. This is not surprising since it is known that SDS can degrade collagen, causing fragmentation and swelling of tissues [Bodnar et al, 1986;Gilbert et al, 2006]. SDS has also been shown to increase tissue extensibility [Mirsadraee et al, 2006].…”
Section: Mechanical Characterizationmentioning
confidence: 98%
“…As shown in table 1 , collagen content in decellularized scaffolds that were prepared using CHAPS decellularization is similar to that of native lung. In contrast, lungs decellularized using SDS detergent, which is anionic and is known to denature proteins more potently than CHAPS [Bodnar et al, 1986;Gilbert et al, 2006], exhibited significantly decreased collagen as compared to native lung tissues, with 787 8 102 g collagen per lung, versus 3,480 8 103 g for native and 4,220 8 480 g for decellularized lung (data for native and CHAPS-treated lung were presented as relative values in Petersen et al [2010]). This loss of collagen with SDSbased decellularization correlated with decreased UTS, which was not observed in the setting of CHAPS-based decellularization and retained collagen ( table 1 ) [Petersen et al, 2010].…”
Section: Collagen and Elastin Contentmentioning
confidence: 99%
“…It was also shown that treatment with SDS resulted in disintegration of collagen fibers 20 as well as fragmentation and swelling of the collagen. 27 Other influences on ECM preservation could be: (1) detergent concentration; (2) duration of treatment; (3) presence of protease inhibitors; and (4) differences in species. 1, 15 In these initial investigations, we developed a perfusion based technique for decellularizing porcine hearts using SDS, a common tissue detergent.…”
Section: Weymann a Et Almentioning
confidence: 99%